Analisis Kepuasan Pengguna Aplikasi Sistem Informasi Rencana Umum Pengadaan di Kabupaten Tabanan Dengan Metode End User Computing Statisfaction dan Technology Acceptance Model - I Wayan Ady Juliantara; I Made Agus Widiana Putra; I Made Agus Oka Gunawan; I Wayan Yudik Pradnyana (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
Information technology has a transformative impact on various aspects of life and covers all fields, even in government activities. The development of information technology has given birth to many new innovations that can help the government in carrying out the procurement process of goods and services. SiRUP is a web-based general procurement plan information system application used to announce the general procurement plan (RUP) implemented by each Regional Apparatus Organization (OPD) in Tabanan Regency. By using the SiRUP application, it will facilitate each OPD in the planning process, transparency and governance of government procurement of goods and services. Achieving the goal of good and transparent government procurement of goods and services, the quality of the system used must be in accordance with what is expected, therefore conducting an evaluation or analysis of satisfaction is very important to do. Based on this, it is necessary to analyze user satisfaction with the SiRUP application which can describe how much user satisfaction is so that recommendations can be given in developing the system according to user needs. Several models and methods have been created to analyze and understand the factors that determine user satisfaction of an application system, including EUCS (End User Computing Statistics) and TAM (Technology Acceptance Model). From the results of the analysis of user satisfaction of the SiRUP application using the EUCS and TAM methods, it was found that the content, form (format), ease of use, and usefulness of the SiRUP application have a positive and significant influence on user attitudes. Relevant information, good design, easy-to-use features, and application benefits are the main factors that increase positive user perceptions. On the other hand, accuracy and timeliness, although they have a positive influence, are not significant on user attitudes, because they are considered basic needs that should be met. In addition, user attitudes are proven to have a positive and significant influence on user satisfaction of the SiRUP application.